The order of concurrent training affects acute immunological stress responses and measures of muscular fitness in female youth judo athletes - Markov, A.; Bussweiler, J.; Baumert, P.; Helm, N.; Rex, M.; Behm, S.; Krüger, T.; Chaabene, H. (European Journal of Sport Science, 2025)
This study aimed to examine the acute effects of concurrent muscle strength and sport-specific endurance exercise order on immunological stress responses, metabolic response, muscular-fitness, and rating-of-perceived-exertion (RPE) in highly trained youth female judo athletes. Thirteen female participants randomly performed two concurrent training (CT) sessions; strength-endurance and endurance-strength. Immune response, metabolic response, muscular fitness (i.e., countermovement jump-derived force and power [CMJ-force and CMJ-power]), and RPE were measured at different time points (i.e., PRE, MID, POST, POST6h, and POST22h). There were significant time × order interactions for lymphocytes (p = 0.006, ES = 1.31), granulocyte-lymphocyte ratio (p = 0.002, ES = 1.56), and systemic inflammation index (p = 0.029, ES = 1.11), blood glucose and lactate (p < 0.001, ES = 2.09 and p = 0.0018, ES = 1.51, respectively), CMJ-force (p = 0.033, ES = 1.26), and CMJ-power (p = 0.007, ES = 1.40) as well as RPE (p < 0.001, ES = 2.05). CT-induced acute (i.e., POST) but not delayed (i.e., POST6h and POST22h) order-dependent immune cell count alterations in highly trained youth female judo athletes. All markers of the immune system went back to baseline values at POST22h. Metabolic responses were slightly higher following the endurance exercise (irrespective of the applied exercise order). CMJ-measures and RPE fluctuated during both CT sessions but returned to baseline 6 h post-exercise.